Comment on Schosser (2018) "Incentive systems for risky investment decisions under unknown preferences: Ortner et al. revisited" - Julia Ortner (Games, 2018)
Schosser (Games 2018, 9, 26) claims to have found an alternative solution to design appropriate performance measures than the State-Contingent Relative Benefit Cost Allocation (RBCA) introduced by Ortner et al. (Management Accounting Research 2017, 36, 43-50), which he states is simpler and more powerful. However, this note reveals that the performance measures proposed by Schosser are, in fact, a specific subset of State-Contingent Robust RBCA performance measures and thus do not represent a new solution.
Keywords: 330; investment decision; performance measure; relative benefit cost allocation